Rumex tunetanus (Polygonaceae): rediscovery of an endangered Tunisian endemic - Ghrabi-Gammar, Zeineb; Muller, Serge D.; Rouissi, Maya; Jilani, Imtinen Ben Haj; Rhazi, Laïla; Bélair, Gérard De; Saad-Limam, Semia Ben; Daoud-Bouattour, Amina (Phytotaxa, 2017)
Rumex tunetanus is a strictly endemic species occurring on the banks of the dried lake of Sejenane (NW-Tunisia) which was discovered in 1888 (published in 1899), but never seen until our rediscovery in 2009. This finding allowed us to give a more complete morphological description of the species, as well as to specify its ecological preferences and conservation status. A lectotype preserved at P was designated for the name Rumex tunetanus.